SOCIAL MEDIA FOR SOCIALLY RESPONSIBLE COMPANY IN INDONESIA: ANALYSIS OF KOMPAS 100’S TWITTER PROFILES AND THEIR CSR RATINGS - Khairunnisa, Carla; Nainggolan, Yunieta Anny (Journal of Business and Management, 2018)
Abstract. The development of technology and information, causing more people to be critical of the company's activities include corporate social responsibility. The convenience served by social media allows the companies to communicate with stakeholder with more effective and efficient. The socially responsible companies are expected to utilize social media to communicate with their stakeholders. This research observes the relation between CSR index score and social media activity for companies in Indonesia. Interestingly, the result of this research shows that socially responsible companies are not more proactive in adopting the social media, nor adopting the social media promptly. The result of this research showed that the companies with higher CSR index score correspond negatively with adoption and prompt adoption of social media. However, the result of this research shows that the socially responsible companies are more active in suggesting topics using hashtag in social media. KEYWORDS: Social Media, Twitter, CSR, Probit Regression, Ordinary Least Square (OLS) Regression, Kompas 100.